2010
DOI: 10.1111/j.1755-148x.2010.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel nonsense mutation on the Pax3 gene in ENU-derived white belly spotting mice and its genetic interaction with c-Kit

Abstract: SummaryIn the course of a large-scale screening program of N-ethyl-N-nitrosourea mutagenesis, we isolated two semidominant mutation lines with white belly spotting, named as wps and wbs. Direct sequencing detected a nucleotide G-to-A transversion in exon 2 of the c-Kit gene in wps, which resulted in a missense D60N mutation. Another mutant, wbs, was mapped to chromosome 1 by genome-wide linkage analysis. In 93 meioses, the wbs locus was confined to a 5.2-Mb region between D1Mit380 and D1Mit215, including the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Additional experiments demonstrated that signaling via the Kit receptor modulates Mitf and is required for Mitf-dependent induction of Tyrosinase ( Tyr ), a rate limiting enzyme in melanin production (Hou et al, 2000). The study of double heterozygous pigmentation mutants has also revealed the presence of synergistic interactions resulting from underlying molecular interactions between Mitf and the anti-apoptotic factor Bcl2 (McGill et al, 2002) and between the transcription factors Pax3 and Kit (Guo et al, 2010)…”
Section: Discussionmentioning
confidence: 99%
“…Additional experiments demonstrated that signaling via the Kit receptor modulates Mitf and is required for Mitf-dependent induction of Tyrosinase ( Tyr ), a rate limiting enzyme in melanin production (Hou et al, 2000). The study of double heterozygous pigmentation mutants has also revealed the presence of synergistic interactions resulting from underlying molecular interactions between Mitf and the anti-apoptotic factor Bcl2 (McGill et al, 2002) and between the transcription factors Pax3 and Kit (Guo et al, 2010)…”
Section: Discussionmentioning
confidence: 99%
“…Pax3 is able to inhibit the expression of trp2 , responsible for the conversion of L-dopachrome into 5,6-dihydroxyindole-2-carboxylate. This ensures high levels of mitf expression to induce melanocyte differentiation [29], [30] but at the same time prevents terminal differentiation. In the presence of β-catenin, the action of pax3 to block trp2 transcription is missing [31] and then trp2 contributes to melanocyte differentiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8). As occurs with mitf, pax3 also promotes and inhibits melanogenesis through transcriptional regulation of cKit [30]. CKit plays a critical role in melanocyte physiology by influencing melanogenesis, migration and survival of these cells [32] and it is primarily expressed in the melanized melanophores [13].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the physiological role of Kit, we analysed the metabolic phenotypes of the Wps mouse strain, which carries a loss-of-function mutation in the Kit gene 25 . The Wps mutation does not affect the splicing of GNNK À versus GNNK þ Kit, but does significantly inhibit tyrosine kinase activity and downstream Akt and Erk signalling of Kit both in vitro and in vivo ( Supplementary Fig.…”
Section: Scf/kit Expression Is Altered In Obese Animals and Humansmentioning
confidence: 99%